Business Development for Companies Procuring Goods and Services through Government e-Catalog: Case Study on CV Budiman Mulya - Mulyadi, Riki; Kaniawati, Keni (International Journal of Marketing & Human Resource Research, 2025)
This study aims to analyze the internal and external business structure of CV Budiman Mulya and formulate an appropriate development strategy within the context of the government goods and services procurement system through e-Catalog. This study uses a descriptive qualitative approach with interview, observation, and documentation techniques. The analysis is conducted using a SWOT approach to identify the strengths, weaknesses, opportunities, and threats faced by the company. The results show that CV Budiman Mulya has key strengths in a clear organizational structure, an integrity-based work culture, mastery of the SPSE and e-Catalog systems, and supporting digital assets. On the other hand, weaknesses are found in aspects of functional specialization, HR training, and manual documentation systems. The resulting strategies include aggressive (SO), diversification (ST), defensive (WO), and survival (WT) strategies, all of which are aimed at strengthening the company's competitiveness in the national digital procurement ecosystem. This study also designs a Business Model Canvas (BMC) consisting of nine main blocks, which represent the integration of the company's business strategy with a technology-based procurement system. These results provide practical contributions in the formulation of business strategies for MSMEs in the procurement sector as well as theoretical implications for digital-based business development models in the public sector.